Quantifying Serum Level of Glycochenodeoxycholic Acid Using High Performance Liquid Chromatography in Obstructive Jaundice Patients. (5th November 2012) - Lalisang, Toar J. M.; Sari Wiria, Metta Sinta; Sutikno, Vivian; Louisa, Melva; Estuningtyas, Arie
Abstract : Introduction. Accumulation of glycochenodeoxycholic acid (GCDC) in serum has a clinical significance as an inductor of pathological hepatocyte apoptosis, which impairs liver function. Inhibition of GCDC accumulation can be used as a marker in therapy. This study was aimed to quantify the serum level of GCDC in obstructive jaundice patients. Methodology. GCDC acid level in the serum was quantified using high performance liquid chromatography (HPLC) technique according to Muraca and Ghoos modified method. It was performed before and after decompression at day 7 and day 14. The sample was extracted with solid phase extraction (SPE) technique on SPE column. The results were analyzed using SPSS V 16.0 (P < 0.05 ) and quantified with standard curve on GCDC acid. Result. There were 21 cases with range of GCDC acid serum level before decompression was 90.9 (SD 205.5) μ mol/L and day 7 after decompression decreased to 4.0 (SD 46.4) μ mol/L and then increased to 11.3 (SD 21.9) μ mol/L (P < 0.05 ). This method could separate GCDC acid on serum with good resolution, high precision and accuracy, and linear calibration curve on measured level range. Conclusion . HPLC can quantify GCDC acid serum on obstructive jaundice patients and can be used to support its pharmacokinetic study.